2011
DOI: 10.1007/s11738-011-0835-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drought stress-responsive genes from drought-tolerant groundnut cultivar (Arachis hypogaea L. cv K-134) through analysis of subtracted expressed sequence tags

Abstract: Drought is one of the major abiotic stresses limiting crop productivity in arid and semi-arid regions and influences many aspects of plant development. Groundnut (Arachis hypogaea L.) is an important oil yielding crop and considered as relatively drought tolerant. In this study, two groundnut cultivars were first tested for their drought tolerance based on physiological marker attributes such as relative water content, total chlorophyll content, cell membrane stability and free proline content and identified c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Among these unigenes, 194 (68.3 %) had significant BLASTN hits (using default parameters) with at least one contig present in A. duranensis 454 libraries, suggesting that A. duranensis and A. magna share some of the genes involved in the signaling pathways in response to water deficit. BLASTX and Blast2GO algorithms revealed that approximately half of these sequences (48 %) had significant matches to genes encoding proteins with known functions, in accordance to previous Arachis transcriptome studies on peanut or AA genome Arachis species (Ding et al 2014 ; Govind et al 2009 ; Guimaraes et al 2012 ; Guo et al 2008 ; Li et al 2014 ; Proite et al 2007 ; Ranganayakulu et al 2011 ; Tirumalaraju et al 2011 ). Therefore, these A. magna unigenes represent the first functionally annotated transcriptome analysis for a BB genome of an Arachis species.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Among these unigenes, 194 (68.3 %) had significant BLASTN hits (using default parameters) with at least one contig present in A. duranensis 454 libraries, suggesting that A. duranensis and A. magna share some of the genes involved in the signaling pathways in response to water deficit. BLASTX and Blast2GO algorithms revealed that approximately half of these sequences (48 %) had significant matches to genes encoding proteins with known functions, in accordance to previous Arachis transcriptome studies on peanut or AA genome Arachis species (Ding et al 2014 ; Govind et al 2009 ; Guimaraes et al 2012 ; Guo et al 2008 ; Li et al 2014 ; Proite et al 2007 ; Ranganayakulu et al 2011 ; Tirumalaraju et al 2011 ). Therefore, these A. magna unigenes represent the first functionally annotated transcriptome analysis for a BB genome of an Arachis species.…”
Section: Resultssupporting
confidence: 83%
“…Peanut has a large tetraploid genome, and its genetic studies have been hindered over the years by the scarcity of genomic resources (Brasileiro et al 2014 ; Holbrook et al 2011 ; Pandey et al 2012 ) such as physical maps, a comprehensive transcriptome database, and a fully sequenced genome, which is now on the verge of being accomplished by the International Peanut Genome Initiative (IPGI; http://www.peanutbioscience.com/homepage.html ). In addition, only recently, studies identifying genes associated with drought stress responses using transcriptome approaches for the genus Arachis have become available (Ding et al 2014 ; Govind et al 2009 ; Guimaraes et al 2012 ; Jain et al 2001 ; Li et al 2014 ; Luo et al 2005 ; Ranganayakulu et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4,22,23]. However, to our knowledge, no massal transcriptome analysis in stressed wild Arachis is available.…”
Section: Introductionmentioning
confidence: 99%
“…Functional genomics studies, using microarrays and subtractive libraries (SSH), identified genes potentially associated to stress responses to C. personatum and drought stress in Arachis spp. [ 3 , 4 , 22 , 23 ]. However, to our knowledge, no massal transcriptome analysis in stressed wild Arachis is available.…”
Section: Introductionmentioning
confidence: 99%
“…As a legume crop, groundnut cultivation improves soil fertility and productivity by fixing atmospheric nitrogen [13]. Additionally, the plant's haulm and by-products have value as a feed for livestock [14,15]. The groundnut value chain in Burkina Faso employs a significant number of people and contributes substantially to the economy [4,16] and to family wellbeing [6,17].…”
Section: Introduction: the Importance Of Groundnut In Burkina Fasomentioning
confidence: 99%